Extratos vegetais e compostos voláteis no controle de Monilinia fructicola in vitro e da podridão parda na pós-colheita de pêssegos - Baseggio, Ediane Roncaglio (2016)
The Monilinia fructicola causes the brown rot in peaches and becomes a limiting factor in the production and quality of peaches, it is the fruits of rot before ripening or decrease your post-harvest period. Thus alternative products such as plant extracts and essential oils have the potential to control this disease. Thus they were developed two works being an in vitro and another in post-harvest peaches seeking to evaluate the effect of garlic extract (Allium sativum), rue (Ruta graveolens), coot (Baccharis trimera), grass - lemongrass (Cymbopogon citratus) eucalyptus (Eucalyptus globulus) and neem (Azadirachta indica), on the fungus Monilinia fructicola and control of brown rot on fruit. The first job was in vitro using aqueous extracts autoclaved and not autoclaved on mycelial growth and germination of conidia of M. fructicola. The experimental design was completely randomized, with five replications, and the experimental unit composed of a Petri® board. The fungus was isolated from infected fruit on PDA (Potato-Dextrose-Aagar). The aqueous extracts were made using 20 g of plant material per 100 mL of distilled water. After diluted in PDA medium at concentrations of 0,5, 10, 15 and 20%. With the solidification placed 0,5 cm diameter disks containing the mycelium and conidia of the pathogen in the center of each plate. To evaluate the essential oil evaluated the dosage of 20 μL of each essential oil obtained by hydrodistillation, applied to filter paper sterile, fixed in the center of Petri® board cover. Plates were sealed, incubated in BOD at 25 °C and photoperiod of 12 h. After 24 h began measuring the mycelial growth for 7 days. At work in fruit postharvest experimental design was completely randomized, with four replications, and the experimental unit consisting of 7 fruits. The fruits, without injuries and symptoms of brown rot were collected, disinfected and dried at room temperature. Then dipped in the extracts for 30 min and stored in a chamber at 25 °C, 12 h photoperiod for 24 h. After inoculated M. fructicola in concentration 2x105 conidia mL-1. After inoculation fruits were under controlled conditions and after 24, 48 and 72 h inoculation is collected fruit samples of about 1 cm² and 0,5 cm deep. After that was done to measure the protein content, total and reducing sugars, activity of enzymes phenylalanine ammonia lyase (PAL), β-1,3-glucanase and chitinase. Still, it was evaluated the percentage of rottenness of the fruits. The results demonstrated in vitro experiment all the extract and the volatile effect has the potential for reducing the M. fructicola mycelial growth, and such action has specific response in different concentrations. As to the effect on the production of spores, such potential is also shown, with the exception of arruda extract. Among the extracts evaluated the garlic has shown highlighted in the suppression of mycelial growth and sporulation of the pathogen. In the experiment in post-harvest the results showed that the extracts evaluated, have the potential to induce resistance to brown rot of fruits, activating the chitinase enzymes and phenylalanine ammonia lyase. However, the garlic extract, besides demonstrating detachable potential to activate such defense mechanisms, works to reduce the peach fruit rot caused by M. fructicola.